G14(P) What Do Senior Paediatric Trainees Want from Simulation in Yorkshire? Training Needs Assessment Survey. (4th June 2013) - Ahmed, A; Moore, H; Purva, M; Clark, S
Abstract : Introduction: Our School of Paediatrics was among the first to embrace Simulation to deliver parts of the RCPCH curriculum. A comprehensive programme of simulation-based training has already been developed for Level I paediatric trainees in the region. A survey was conducted to explore the training needs of senior paediatric trainees (ST6–8) in the region. Methods: A web-based questionnaire was sent to all Level III trainees in the region (N = 129) to determine their experience of simulation-based training. Trainees also assessed their confidence level on a 1 to 4 scale in managing some clinical situations. Subsequently, we explored results of the survey in a focus group with Level III trainees. Results: Thirty-nine responses were received. Most trainees (82%) had not attended an immersive simulation course previously. While the majority (85%) of trainees have received some training in handling difficult communication, their reported confidence in managing difficult communication was low: withdrawal of care in a preterm neonate, discussion of DNAR decision in a child, and leading debriefing with team after a failed resuscitation (Figure 1 ). Managing conflict at work was highlighted as a deficiency in training as 41% of trainees had received no formal training at all. Other areas, which were highlighted as training need by trainees in the focus group, were human factors training, training in interview skills and difficult communication scenarios like handling complaints and conflict at work. Discussion: Trainees feel more confident in scenarios involving management of acute conditions than difficult communication, but even in these overall confidence levels are low. It is concerning that trainees do not feel prepared for the role of a new consultant. There is growing evidence that patient care and safety can be improved by regular simulation-based training programmes 1 . We intend to fulfil this training requirement by providing a curriculum–referenced course incorporating human factors and care of the acutely unwell children. Reference: Shapiro MJ, Morey JC, Small SD, Langford V, Taylor L, Suner S, Salisbury ML, Simon R, Jay GD. Simulation based teamwork training for emergency department staff: does it improve clinical team performance when added to an existing didactic teamwork curriculum Qual Saf Health Care 2004; 13:417–421 doi:10.1136/qshc.2003.005447